Intelligence Profile and Executive Function Between Children with Typical Development and Children with High-Functioning Autism Spectrum Disorder - Faradila Azka; Donny Hendrawan (Jurnal Psikologi, 2023)
Intelligence plays a significant role in determining the severity of Autism Spectrum Disorder (ASD), thus understanding intelligence among children with ASD is important to guide planning of appropriate interventions. Scores on IQ tests as well as intelligence sub-components between ASD and typically developed (TD) children, reflect distinct underlying cognitive processes. Therefore, a comprehensive investigation of the neuropsychological aspects of children ASD may better refine our understanding of the cognitive abilities among children with ASD. The current cross-sectional study investigated differences in intelligence profiles and executive function among children with TD children and children with High-Functioning Autism Spectrum Disorder (HFASD). A total of 34 participants met criteria for inclusion with 24 participants in the TD group, and 10 in the HFASD. Some of the measures which were used included the SB-LM, Executive Function Indonesia (EFI), and Autism Spectrum Quotient: Children's Version (AQ-Child). Data were analysed using Spearman correlation and Mann-Whitney test. Results showed no differences in the intelligence profile in both groups, yet significant differences were found in the composite EF, Inhibitory Control, and Cognitive Flexibility. Additionally, there was a difference in the correlation of intelligence and EF variables between the two groups. Thus, it can be concluded that both groups show qualitatively different cognitive processes. A recommendation derived from these results is that comprehensive EF assessment and treatment should be conducted as part of the global evaluation of ASD patients, primarily to design an intervention to enhance their academic domain.